Dose and aging effect on patients reported treatment benefit switching from the first overactive bladder therapy with tolterodine ER to fesoterodine: post-hoc analysis from an observational and retrospective study - Castro-Diaz David; Miranda Pilar; Sanchez-Ballester Francisco; Lizarraga Isabel; Arumí Daniel; Rejas Javier (BMC Urology, 2012)
Abstract Background Previous randomized studies have demonstrated that fesoterodine significantly improves the Overactive Bladder (OAB) symptoms and their assessment by patients compared with tolterodine extended-release (ER). This study aimed to assess the effect of aging and dose escalation on patient-reported treatment benefit, after changing their first Overactive Bladder (OAB) therapy with tolterodine-ER to fesoterodine in daily clinical practice. Methods A post-hoc analysis of data from a retrospective, cross-sectional and observational study was performed in a cohort of 748 OAB adults patients (OAB-V8 score ≥8), who switched to fesoterodine from their first tolterodine-ER-based therapy within the 3–4 months before study visit. Effect of fesoterodine doses (4 mg vs. 8 mg) and patient age (<65 yr vs. ≥65 yr) were assessed. Patient reported treatment benefit [Treatment Benefit Scale (TBS)] and physician assessment of improvement with change [Clinical Global Impression of Improvement subscale (CGI-I)] were recorded. Treatment satisfaction, degree of worry, bother and interference with daily living activities due to urinary symptoms were also assessed. Results Improvements were not affected by age. Fesoterodine 8 mg vs. 4 mg provides significant improvements in terms of treatment benefit [TBS 97.1% vs. 88.4%, p < 0.001; CGI-I 95.8% vs. 90.8% p < 0.05)], degree of worry, bother and interference with daily-living activities related to OAB symptoms (p <0.05). Conclusions A change from tolterodine ER therapy to fesoterodine with dose escalation to 8 mg in symptomatic OAB patients, seems to be associated with greater improvement in terms of both patient-reported-treatment benefit and clinical global impression of change. Improvement was not affected by age.